Effects on perceived pain and somatosensory function after transcutaneous neuromodulation in patients with chronic low back pain: a quasi-experimental study with a crossover intervention - Selva-Sarzo, Francisco; Sánchez Romero, Eleuterio A.; Cuenca-Zaldívar, Juan Nicolás; García-Haba, Beatriz; Akiyama, Claudio; Sillevis, Rob; Fernández-Carnero, Samuel (Frontiers in Pain Research, 2025)
BackgroundTranscutaneous magnetic neuromodulation is a noninvasive technique that may influence pain perception and mobility by modulating epidermal afferents and autonomic nervous system activity. However, its effects on chronic non-specific low back pain (CNSLBP) remain unclear.ObjectiveThis study evaluated the effects of transcutaneous neuromodulation applied to the lumbar spine on the pressure pain threshold (PPT) and ankle dorsiflexion range of motion (DROM) in patients with chronic non-specific low back pain.MethodsA single-group prospective cohort study with crossover intervention was conducted from June to December 2021. A convenience sample of 39 patients with CNSLBP was included in this study. Each participant received two interventions in a randomized sequence: transcutaneous neuromodulation tape with magnetic particles (TMP) and placebo kinesiology tape (KT). A one-week washout period was implemented between the interventions. TMP was applied at the lumbar spinal levels for 48 h, following standard recommendations for neuromodulation frequency (constant exposure via magnetic particles), intensity (low-energy field), and time (continuous exposure over two days). The primary outcome measure was PPT assessed using algometry, and the secondary outcome was DROM assessed using the Lunge Test. This study adhered to the STROBE guidelines for observational studies.ResultsThe Lunge test revealed no significant group–time interaction [F(2, 152) = 0.132, p = 0.752], with a small effect size [F(1, 76) = 0.699, p = 0.406]. The main effect group showed a small non-significant effect [ηp2 = 0.009 (0, 0.091)]. However, the main effect of time was significant [F(2, 152) = 147.669, p = 0.001] with a large effect size [ηp2 = 0.66 (0.54, 0.735)]. Pairwise leg comparisons were not significant (p > 0.05). For the pressure pain threshold, significant differences (p < 0.05) with moderate to large effect sizes were observed. PPTs varied by vertebral level, with significant differences in site-specific comparisons between specific levels.ConclusionsTranscutaneous neuromodulation using TMP applied to the lumbar spine reduces perceived pain and increases ankle dorsiflexion range of motion in patients with CNSLBP. These findings suggest that epidermal afferent modulation may contribute to pain relief and motor function enhancement, providing a novel approach for noninvasive pain management.